1992
DOI: 10.2307/3869568
|View full text |Cite
|
Sign up to set email alerts
|

A Meristem-Related Gene from Tomato Encodes a dUTPase: Analysis of Expression in Vegetative and Floral Meristems

Abstract: A meristem-specific gene coding for deoxyuridine triphosphatase (EC 3.6.1.23) (dUTPase) in tomato was isolated, and its developmental expression in vegetative and floral apices was monitored. An 18-kD polypeptide, P18, was isolated as a consequence of its accumulation in arrested floral meristems of anantha mutant plants. The corresponding cDNA isolated from an expression library exhibited a 40 to 60% similarity with the pseudoprotease sequences of poxviruses, genes that have been suggested to encode dUTPases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…At least four to five layers of apical cells were labeled, indicating that cells in all apical meristematic layers (LI, LII, and LIII) express TM5 and TM6. Provascular cells, which at this stage already express the dUTPase gene (Pri-Hadash et al, 1992), were not yet labeled, but were extensively marked during organogenesis (Figures 2A to 2D).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…At least four to five layers of apical cells were labeled, indicating that cells in all apical meristematic layers (LI, LII, and LIII) express TM5 and TM6. Provascular cells, which at this stage already express the dUTPase gene (Pri-Hadash et al, 1992), were not yet labeled, but were extensively marked during organogenesis (Figures 2A to 2D).…”
Section: Resultsmentioning
confidence: 97%
“…We examined the earliest possible stage of localized TM5 and TM6 gene expression by probing sections of wild-type and ananfha floral meristems at the preorganogenesis stage with labeled TM5 or TM6 antisense RNA. Meristematic organs of the ananfha mutant inflorescences are arrested at the preorganogenesis stage (Helm, 1951) and exhibit patterns of gene expression characteristic of floral primordia (Shahar et al, 1992;Pri-Hadash et al, 1992). Localization of TM5 RNA in the early preorganization stage of wild-type floral buds is shown in Figure lA, and localization of TM6 RNA in early wild-type floral buds and in ananfha floral meristems is depicted in Figures 18 and 1C.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of dUTPase in plants suggest that expression is linked to the rate of proliferation, as demonstrated by a close association of dUTPase activity and replicative vegetative and floral meristem regions (16,17). Recently, the dUTPase gene was isolated from the human fungal pathogen, Candida albicans, the expression of which is governed in part by an MluI cell cycle box element located in the promoter region (18).…”
mentioning
confidence: 99%
“…A growing number of dUTPases from various sources have been reported and several sequences have been published (Bj6rnberg et al, 1993;Bergman et al, 1994: Elder et al, 1992Broyles, 1993;Roseman et al, 1996;Giroir & Deutsch, 1987;Climie et al, 1994;McIntosh et a/., 1992McIntosh et a/., , 1994Pri-Hadash et al, 1992;Wagaman et al, 1993). Protein sequence comparisons between the E. coli enzyme (Lundberg, Thoresson et al, 1983) and viral dUTPases (McGeoch, 1990) revealed five conserved motifs scattered along the sequence, indicating that those parts might be important for catalytic function and/or stability.…”
Section: Introductionmentioning
confidence: 99%